Student learning about digital electronics through software teaching practices - Castro, George Harinson Martins; Sousa, Ana Cláudia Gouveia de; Costa, Kiara Lima; Rodrigues, Igor Lima (Faculdade de Filosofia e Ciências, 2021)
Currently, technologies are present in several educational levels with the aim of improve teaching and students learning process, as they mostly belong to the so-called digital native generation, also considering those who do not usually use the technologies in your everyday actions. Thus, this article presents an exploratory research about the use of simulator software in practical classes of digital electronics, carried out in the emergency remote teaching (ERT) in 2020, due to the COVID-19 Pandemic. This research aimed to identify students' learning and perceptions, using simulators in practical classes during remote teaching in times of pandemic. This study was developed on an IFCE campus, in the Digital Electronics classes. Two software were chosen, Logisim, for desktop computers, and Make it True, for mobile devices, both totally free. Through simulations made with them, students performed the practices related to the subjects of the discipline, whose necessary analogical practices were limited by the ERE. It is worth noting that they were carried out after a theoretical explanation of the contents. Students worked throughout the discipline with the applications, and, in the end, answered a questionnaire with multiple choice and essay questions about many learnings about such applications. As a result, it was possible to state that students learned the contents of the discipline, through the use of software during the practical classes, and appreciated the potential of the experience.